Impact of Ivabradine on Central Aortic Blood Pressure and Myocardial Perfusion in Patients With Stable Coronary Artery Disease. Issue 6 (December 2015) - Dillinger, Jean-Guillaume; Maher, Vincent; Vitale, Cristiana; Henry, Patrick; Logeart, Damien; Manzo Silberman, Stephane; Allée, Guillaume; Levy, Bernard I.
Abstract : Abstract—: Treatment of hypertensive patients with β-blockers reduces heart rate and decreases central blood pressure less than other antihypertensive drugs, implying that reducing heart rate without altering brachial blood pressure could increase central blood pressure, explaining the increased cardiovascular risk reported with β-blocker. We describe a randomized, double-blind study to explore whether heart rate reduction with the I f inhibitor ivabradine had an impact on central blood pressure. We included 12 normotensive patients with stable coronary artery disease, heart rate ≥70 bpm (sinus rhythm), and stable background β-blocker therapy. Patients received ivabradine 7.5 mg BID or matched placebo for two 3-week periods with a crossover design and evaluation by aplanation tonometry. Treatment with ivabradine was associated with a significant reduction in resting heart rate after 3 weeks versus no change with placebo (−15.8±7.7 versus +0.3±5.8 bpm; P =0.0010). There was no relevant between-group difference in change in central aortic systolic blood pressure (−4.0±9.6 versus +2.4±12.0 mm Hg; P =0.13) or augmentation index (−0.8±10.0% versus +0.3±7.6%; P =0.87). Treatment with ivabradine was associated with a modest increase in left ventricular ejection time (+18.5±17.8 versus +2.8±19.3 ms; P =0.074) and a prolongation of diastolic perfusion time (+215.6±105.3 versus −3.0±55.8 ms with placebo; P =0.0005). Consequently, ivabradine induced a pronounced increase in Buckberg index, an index of myocardial viability (+39.3±27.6% versus −2.5±13.5% with placebo; P =0.0015). In conclusion, heart rate reduction with ivabradine does not increase central aortic blood pressure and is associated with a marked prolongation of diastolic perfusion time and an improvement in myocardial perfusion index. Clinical Trial Registration—: URL:https://www.clinicaltrialsregister.eu . Unique identifier: 2011-004779-35.